2008
DOI: 10.1016/j.ijgo.2008.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Nonobstetric lower genital tract injuries in rural India

Abstract: Severe hemorrhage caused by NOGTIs is potentially fatal in rural settings if treatment is delayed. Prompt resuscitation, early referral, and appropriate surgical intervention can avert both morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 20 publications
3
28
0
14
Order By: Relevance
“…Severe associated urological,intestinal, and bony injuries may be caused by goring, and there is always a high probability of an infection. Hence, all such wounds should be thoroughly washed and debrided, and a meticulous speculum examination of vagina and digital rectal examination are mandatory to arrive at an accurate diagnosis [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe associated urological,intestinal, and bony injuries may be caused by goring, and there is always a high probability of an infection. Hence, all such wounds should be thoroughly washed and debrided, and a meticulous speculum examination of vagina and digital rectal examination are mandatory to arrive at an accurate diagnosis [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Many cases may resolve with a minimal medical intervention, but the majority cases have severe lacerations, and require hospitalization and blood transfusion, while some may be fatal. Labial hematoma usually requires conservative management except when there is continuous bleeding [2]. Evacuation of hematoma along with suturing is the mainstay of management in the presence of bleeding from the wound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injuries to the female external genitalia accounted for one-third of all paediatric injuries and nearly 20% of all adult injuries. Given our findings, and with only two case series of vulvovaginal trauma identified in the literature, the risk of perineal and vaginal trauma in girls associated with bicycles is under-reported and likely underappreciated by physicians and by experts involved in injury prevention initiatives 9 10. We believe further attention should be paid to this common type of GU injury caused by bicycles.…”
Section: Discussionmentioning
confidence: 68%
“…Prospective studies in gynaecological trauma services (excluding obstetric injuries) have shown coital injuries to represent 32.7% of genital injuries (Jana et al, 2008). Legally, these injuries are classified according to whether intercourse was consensual (i.e.…”
Section: Physical Assaultmentioning
confidence: 99%